«Implantation window» disturbance in patients with hyperplastic processes of endometrium - Parnytska, O. I. (Pathologia, 2014)
Introduction There is an increasing interest in the role of hyperplastic processes of endometrium in the “implantation window” disturbance and unsuccessful implantation rate. The endometrium represents a barrier to implantation except under appropriate and defined hormonal conditions. There is no doubt that endometrium has an important role for embryo implantation at early stages of development. Successful implantation requires a functionally normal embryo at the blastocyst stage and receptive endometrium, while the communication between them is also vital. Endometrium shows dynamic and cyclic morphological changes throughout the follicular phase and in the secretory phase. The progesterone-driven differentiative changes in the endometrial epithelium lead to the ‘opening’ of the “window of receptivity” for blastocyst implantation. Morphologically, progesterone-dependent apical cellular protrusions known as pinopods (uterodomes) become visible by scanning electron microscopy on 20th–21st days of human menstrual cycle and then are lost. Materials and methods A total of 180 endometrial specimens from women with simple hyperplasia (I gr.), endometrial polyps (II gr.) and asynchronous endometrium (III gr.) have been examined by scanning electron microscopy. Biopsies were obtained from fundus of the uterus and processed for light and scanning electron microscopy. Tissues for light microscopy were fixed in 1,25% glutardialdehyde, embedded in paraffin, sectioned and stained with hematoxylin and eosin. Results In I group with simple hyperplasia the ratio of glands and stroma is now increased. Most or all of the endometrial glands are more or less cystically dilated and lined by pseudostratified, highly proliferating epithelium with enlarged, elongated, nuclei in scanty, basophilic cytoplasm. Mitoses are frequent in the epithelium. II group shows endometrial polyps with proliferation of stromal cells incorporating a non-neoplastic glandular component. They were pedunculated with a central fibrovascular core which, when visible in the plane of the section, will be a characteristic diagnostic sign.The hyperplastic polyps contained areas of simple hyperplasia without atypia. In the III group morphology of the deficient secretory phase with coordinated true delay was evaluated and there were no significant changes in ciliated cells quality and quantity. We revealed only “implantation window” disturbance as delay in pinopodes formation or absence of uterodomes. Present study revealed isolated pathological changes of ciliated cells and its conjunction with abnormalities in pinopodes formation (“implantation window”) in women with simple hyperplasia (I group) and polyps (II group) in compare to endometrium of III group. Discussion We observed that significant increasing of ciliated cells quantity, cilliar hyperplasia and irregular distribution in women with simple hyperplasia of endometrium can cause breaking of embryo implantation (apposition and attachment) even in case of regular pinopodes formation.